Schlussfolgerungen aus der Theorie endogenen Wachstums für eine ausgleichende Regionalpolitik - Bröcker, Johannes (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
According to New Growth Theory one can not rely on the convergence mechanisms inherent in traditional constant returns to scale models in neoclassic. Convergence as well as divergence is possible, in general, depending on the assumptions about technology, factor mobility and ease of knowledge diffusion. The paper shows by a two-regions endogenous growth model when divergence, convergence or stable centre-periphery structure emerges. Based on this model, regional policy aiming at regional equity — though desirable for distributive reasons — contradicts the efficiency objective: as far as the spatial allocation in market equilibrium is inefficient at all, more inequality rather than less is required to enhance efficiency.
Keywords: Article